New technologies applied to heritage teaching. - Rascón Marqués, Sebastián; Sánchez Montes, Ana Lucía (Pulso. Revista de educación, 2008)
This paper explores, from the authors experiences, how new technologies have been used during the last two decades to understand archaeological and historical sites. Authors not only present a critical evaluation on the possibilities and real outcomes of their use, but also provide with a methodology for its implementation. Finally, an overview of productions in this field is included.
Keywords: Heritage Education; New Technologies; 3D. Archaeology; Visualization